Study on the Assimilation of Huyula and Pogogutat Culture in the Gorontalo and Bolaang Mongondow Border Areas - Lukman Arsyad; Sumarlin Adam (Journal La Sociale, 2023)
This study examines the assimilation of Huyula culture in Gorontalo and Pogogutat tradition in Bolaang Mongondow, with a specific focus on the border regions between the two. Ongoing research is being conducted to investigate the cultural dynamics and alterations that occur due to reduced spatial, temporal, and interpersonal distances. This research used a qualitative ethnographic methodology to ascertain the extent of cultural assimilation in the two adjacent regions, assess the assimilation of the Huyula and Pogogutat cultures, and identify the factors that contribute to this phenomenon. Theoretical framework encompasses definitions, features, components, and the concept of cultural assimilation within the realm of culture. The present paper explores the Huyula culture of Gorontalo and the Pogogutat tradition of Bolaang Mongondow, providing insights into its historical roots, societal practices, and significance within the local community. In order to provide a comprehensive understanding of the subject matter, this study also explores previous research conducted on cultural traditions and local knowledge in both regions.